Comparison on the Security of Biometrics. (August 2020) - Ye, Huichao; Pei, Roy; Mo, Zongyin; Zheng, Qingmin; Chen, Huanzhong
Abstract: With the increasing requirements for public safety in modern society, the traditional authentication method is far from meeting the needs of protecting human safety. The biological features represented by human face, iris, veins, voiceprint, etc. play an increasingly important role in identity recognition, and are relatively found and get more attention. This article compares the advantages and disadvantages of the three biometric recognition technologies of human face, iris and vein, compares the security of each biometric recognition technology and makes a prospect of the biometric recognition technology.